Evaluation of the dynamics of microalgae population structure and process performance during piggery wastewater treatment in algal-bacterial photobioreactors. (January 2018) - García, Dimas; Posadas, Esther; Blanco, Saúl; Acién, Gabriel; García-Encina, Pedro; Bolado, Silvia; Muñoz, Raúl
Graphical abstract: Highlights: Efficient PWW treatment and Zn biosorption occurred regardless of the microalgae. Rapid variations in microalgae population structure during PWW treatment. Chlorella sp. exhibited a high tolerance to the pollutants present in PWW. The acclimation of native microalgae resulted in the highest biomass concentrations. Abstract: The dynamics of microalgae population during piggery wastewater (PWW) treatment in four open photobioreactors operated at 27 days of hydraulic retention time, and inoculated with Chlorella sp. (R1), Acutodesmus obliquus (R2), Oscillatoria sp. (R3) and in the absence of inoculum (R4), were evaluated for 6 months. In addition, the algal-bacterial biomass concentration, removal of organic matter, nutrients and heavy metals were also assessed. The results revealed a high diversity and rapid variations in the structure of microalgae populations, Chlorella sp. being dominant in R4 throughout most of the operational period. Steady state average biomass concentration ranged from 2445–2610 mg/L in R1–R3 to 3265 mg/L in R4. No significant differences were recorded in the removal efficiencies (REs) of total organic carbon (86–87%), inorganic carbon (62–71%), total nitrogen (82–85%) and total phosphorous (90–92%). Finally, Zn-REs accounted for 26% in R3, 37% in R2, and 49% in R1 and R4.